A New Species of the Genus Berytoniscus Vandel, 1955 (Isopoda: Oniscidea: Berytoniscidae), and First Record of the Family Berytoniscidae from Iran - Bakhshi, Yaser; Sadeghi, Saber (Annales zoologici, 2023)
The family Berytoniscidae is recorded for the first time from Iran and a new species, Berytoniscus persicussp. nov. is described, and its diagnostic characters are illustrated. The specimens were collected from a solutional cave located in south of Iran. Berytoniscus persicussp. nov. is the second species of the genus. The species displays classic troglomorphic characters, such as the absence of eyes and body pigmentation and is, therefore, considered a troglobiotic species.